2015
DOI: 10.1515/hukin-2015-0088
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Anaerobic Performance, Field Tests and Game Performance of Sitting Volleyball Players

Abstract: The aim of this study was to evaluate relationships between anaerobic performance, field tests, game performance and anthropometric variables of sitting volleyball players. Twenty elite Polish sitting volleyball players were tested using the 30 s Wingate Anaerobic Test for arm crank ergometer and participated in six physical field tests. Heights in position to block and to spike, as well as arm reach were measured. Players were observed during the game on the court in terms of effectiveness of the serve, block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 5 publications
1
45
1
2
Order By: Relevance
“…One essential fundamental step of the scientific approach is systematic collection of empirical data of various phenomena. Previously, many sports scientists have investigated various characteristics such as physical fitness, kinanthropometry, psychology, and motor function in elite athletes ( Marszalek et al, 2015 ; Molik et al, 2008 , 2010 , 2012 , 2013 , 2017 ). Elite athletes were studied because it was assumed that since they were at the top level of their sport, their physical fitness, kinanthropometry, and psychology, as well as sports performance skill, would be optimized to perform their sport in an ideal form.…”
Section: Introductionmentioning
confidence: 99%
“…One essential fundamental step of the scientific approach is systematic collection of empirical data of various phenomena. Previously, many sports scientists have investigated various characteristics such as physical fitness, kinanthropometry, psychology, and motor function in elite athletes ( Marszalek et al, 2015 ; Molik et al, 2008 , 2010 , 2012 , 2013 , 2017 ). Elite athletes were studied because it was assumed that since they were at the top level of their sport, their physical fitness, kinanthropometry, and psychology, as well as sports performance skill, would be optimized to perform their sport in an ideal form.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the height of the net is lower, considering the characteristics of the game, since failure to contact either buttocks to the ground is forbidden by rule, we are of the opinion that both upper extremities and upper body height is vital in all parts of the game, particularly in offence and block positions, and they are important criteria in selection of the players. This determination is supported by the research conducted by [9,21].…”
Section: Discussionmentioning
confidence: 69%
“…In a study conducted to determine the relation between the anthropometric variables of 20 elite level Polish sitting volleyball players and anaerobic power, field tests, and game performances, it was reported that the physical fitness and game performances are dependent on the anthropometric variables of the players [21]. Hasanbegovic et al [22] reported that they determined the effects of trainings in sitting volleyball on motor skills by factor analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the literature is examined, it is observed that there are useful and helpful studies conducted on disabled players. Although there are many researches in different disabled sport branches [8][9][10][11][12][13][14], the physical fitness of physically disabled badminton players were not encountered.…”
Section: Introductionmentioning
confidence: 99%